Setting things “right”: right internal mammary artery on anomalous right coronary artery - a case report - M D’Abramo (SAGE Publishing, 2021)
Anomalous aortic origin of a coronary artery (AAOCA) is a rare pathology that may cause episodic ischemia owing to possible vessel compression during systolic expansion of the aortic root. This anomaly can lead to myocardial infarction, malignant arrhythmias and sudden cardiac death (SCD). Several surgical techniques have been described; however, there are no defined guidelines regarding the treatment of AAOCA. We report the case of a 47-year-old woman with ectopic origin of the right coronary artery (RCA) from the left sinus of Valsalva, with an interarterial course of the proximal segment of the artery, running between the aorta and the pulmonary trunk. Revascularization was accomplished by harvesting the right internal mammary artery (RIMA) and anastomosing it to the anomalous RCA, given the small portion of the RCA following an intramural course and our familiarity with the procedure. The RCA was ligated proximal to the anastomosis to avoid the string sign phenomenon. This procedure is safe and fast and can be considered an alternative to coronary reconstruction.